Petrov type of linearly perturbed type-D spacetimes - Araneda, Bernardo Gabriel (2015)
We show that a spacetime satisfying the linearized vacuum Einstein equations around a type-D background is generically of type I, and that the splittings of the principal null directions (PNDs) and of the degenerate eigenvalue of the Weyl tensor are non-analytic functions of the perturbation parameter of the metric. This provides a gauge-invariant characterization of the effect of the perturbation on the underlying geometry, without appealing to differential curvature invariants. This is of particular interest for the Schwarzschild solution, for which there are no signatures of the even perturbations on the algebraic curvature invariants. We also show that, unlike the general case, the unstable even modes of the Schwarzschild naked singularity deform the Weyl tensor into a type-II one.